Fear of Falling Among the Elderly in a Nursing Home: Strongest Risk Factors - Anastasia Putu Martha Anggarani; Raditya Kurniawan Djoar (Jurnal Ners, 2020)
Introduction: The aging process causes a decrease in physical abilities which can cause fall events. Fall events are influenced by fear of falling. Some risk factors of fear of falling were age, gender, balance while walking, use of a walker, depression and a history of previous falls. This study aim was to identify risk factors related to fear of falling among the elderly in nursing home.Methods: A cross-sectional study was used in this study. Respondents were elderly   aged ≥60 years, can communicate well, able to read and write and not being sick which causes balance disorders and pain when walking. Respondents totaled 155 obtained by proportional random sampling. A questionnaire was used to retrieve data such as age, gender, use of a walker, depression, previous fall history and balance walking. Results: The results showed a significant relationship between all of these risk factors with the fear of falling (p <0.05) and the power of significance for each variable was different. The age variable was power significance 0.228, gender C = 0.2, previous fall history C = 0.374, use of a walker C = 0.367, balance walking C = 0.355 and depression rs = 0.196. There are three risk factors most closely associated with fear of falling in terms of balance walking (B = 1.424 Exp(B) = 4,153), use of a walker (B = 1,365 Exp(B) = 3,914) and previous fall history (B = 1.425 Exp(B) = 4.159). These factors had strength of 27%.   Conclusion: Balance walking, use of a walker and previous fall history were the strongest risk factors.